Penerapan Model Pembelajaran Problem Based Learning Menggunakan Strategi Pair Checks untuk Meningkatkan Hasil Belajar Siswa di MAN 2 Boyolali (UPEJ Unnes Physics Education Journal, 2020)
The result of initial observation conducted in MAN 2 Boyolali showed that the students’ learning outcomes on physics subject was still low, so another learning model and strategy are needed, one of them is by innovative cooperation to improve the students’ learning result. Therefore, a learning model of Problem Based Learning is applied using Pair Checks strategy which has big possibility to improve the students’ learning outcomes. This study aims at analyzing the improvement of the students’ cognitive learning outcomes after using Problem Based Learning model with Pair Checks strategy. The study was a quantitative research with experiment method. The population were the students of X IPA MAN 2 Boyolali, the samples were conducted using simple random sampling, with the students from X IPA 1 as the experiment group and the students from X IPA 2 as the control group. The method of data collection were test, observation, and questionnaire. The result shows that the improvement of the students’ cognitive learning outcomes was earned N-gain value from experiment group is 0.59, which belongs to middle criterion, while the control group is 0.29, which belongs to low criterion. The average achievement of affective learning outcomes on the experiment group reachs 75%, which belongs to good criterion, while the control group reachs 59%, which belongs to good enough criterion. The average achievement of psychomotor learning outcomes on the experiment group reachs 74%, which belongs to good criterion, while the control group reachs 55%, which belongs to less good criterion. The analysis result shows that the implementation of Problem Based Learning model using Pair Checks strategy obtains a good response with percentage of 71%. It can be concluded that the students’ cognitive learning result gets significant improvement after applying the learning model of Problem Based Learning using Pair Checks strategy.